The Influences of School Climate, Supervision and Work Motivation on Teacher Professionalism - Yolanda, Septiara; Anisah; Gistituati, Nurhizrah; Sulastri (Indonesian Research Journal in Education |IRJE|, 2024)
This research explored the impact of school climate, academic supervision, and teacher work motivation on teacher professionalism at Pantai Cermin District Elementary School, Solok Regency. Employing a quantitative causality approach and representing the variable relationships through a path diagram, the research encompassed a teacher population of 174 individuals. The sample size, determined using the Cochran formula and Stratified Proportional Random Sampling, resulted in a sample of 82 teachers. The researchers used a questionnaire to collect the data. The findings reveal a direct influence of school climate, academic supervision, and teacher work motivation on teacher professionalism, and an indirect impact of school climate and academic supervision on teacher professionalism is mediated by teacher work motivation at Pantai Cermin District Elementary School, Solok Regency.